Cultural integration in Germany - Amelie F. Constant; Olga Nottmeyer; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2009)
This chapter investigates the integration processes of immigrants in Germany by comparing certain immigrant groups to natives differentiating by gender and immigrant generation. Indicators which are supposed to capture cultural integration of immigrants are differences in marital behavior as well as language abilities, ethnic identification and religious distribution. A special feature of the available data is information about overall life satisfaction, risk aversion and political interest. These indicators are also presented. All of these indicators are depicted in comparison between natives and immigrants differentiated by ethnic origin, gender and generation. This allows visualization of differences by ethnic groups and development over time. Statements about the cultural integration processes of immigrants are thus possible. Furthermore, economic integration in terms of female labor force participation is presented as an additional feature. Empirical findings suggest that differences among immigrants and between immigrants and Germans do exist and differ significantly by ethnic origin, gender and generation. But differences seem to diminish when we consider the second generations. This indicates greater adaptation to German norms and habits, and thus better cultural, socio-economic and political integration of second generation immigrants in Germany.
Keywords: F22; J15; J61; Z13; 330; Cultural integration; immigrants; Germany; ethnic origin; gender; generation; Soziale Integration; Migranten; Generationenbeziehungen; Soziale Norm; Bevölkerung; Deutschland